Synergies with families in the learning era (Journal of Parents and Teachers, 2014)
We are moving from the Information era to the learning era. The economy, business and culture are pushing the school to create a new curriculum where non-cognitive skills are more important than cognitive. To educate these new emotional skills, expressive, digital, empathic, existential and ethical is essential to involve the families under a new paradigm.Synergies with families are generated when there is a solid, reflected and supported institutionally project, when there is an horizontal and participatory methodology, a rereading of the latest educational purposes families must make a clear empathetic leadership and a simple practical channels articulated from tutoring.
Keywords: New paradigm; generation; family and school; tutoring; new skills; innovation; learning era.